Synthetic strigolactone (rac-GR24) alleviates the adverse effects of heat stress on seed germination and photosystem II function in lupine seedlings - Omoarelojie, Luke O; Kulkarni, Manoj G; Finnie, Jeffrey F; Pospíšil, Tomáš; Strnad, Miroslav; Van Staden, Johannes (Plant physiology and biochemistry, 2020)
There is increasing experimental evidence that strigolactones, a class of carotenoid-derived sesquiterpenoid hormones, and their downstream signal components play a role in plant resilience to abiotic stress. Strigolactones positively influence plant coping mechanisms in response to abiotic stressors like drought and high salinity. In this study, we examined the effects of rac-GR24 (a synthetic strigolactone analog) and strigolactone inhibitors on the physiological and molecular responses associated with thermotolerance during seed germination and seedling development in Lupinus angustifolius under heat stress. Photosystem I & II functions were also evaluated via Chl a fluorescence transient analysis in heat stressed lupine seedlings. Our results suggest a putative role for GR24 in mediating tolerance to heat stress during seed germination and seedling development albeit these responses appeared independent of D14-mediated signalling. Seeds primed with GR24 had the highest of all germination indices, enhanced proline content and reduced peroxidation of lipids. GR24 also enhanced the activities of enzymes of the antioxidant and glyoxalase systems in lupine seedlings. The JIP-test indicated that GR24 conferred resistance to heat stress-induced damage to the oxygen evolution complex while also preventing the inactivation of PSII reaction centres thus ensuring PSII thermotolerance.
Keywords: semena rostlinná; reakce na tepelný šok; semenáček; heterocyklické sloučeniny tricyklické; Lupinus; Heat stress tolerance; Germination indices; klíčení; JIP-Test; Glyoxalase system; Heterocyclic Compounds, 3-Ring; Germination; GR24; Seeds; PSII thermotolerance; Strigolactones; Heat-Shock Response; Seedlings; Lactones; laktony; Photosystem II Protein Complex; Antioxidant enzymes; fotosystém II (proteinový komplex); Chlorophyll a fluorescence